Dampak Positif Tiger Parenting Terhadap Kematangan Emosional Anak (Studi Kasus pada Siswa SMA/SMK Di Solo) - Kurnia Ibrahim; Novia Nur Hidayah; Annisa Fitri; Sekar Arum Mawarni; Fissilmy Khaffah Ramadhani (Academica: Journal of Multidisciplinary Studies, 2022)
Tiger parenting is a term that is rarely known by the public where the parenting style that emphasizes children gets high academic achievement. This study was conducted to determine whether the Tiger Parenting style has a positive impact on children's emotional maturity. The research method used is qualitative research with a case study approach and data collection using questionnaires and interviews distributed by researchers. The subjects of this study were 3 high school/vocational high school students in Solo Raya who received the tiger parenting style. The results of this study explain that tiger parenting has a positive impact on the emotional maturity of high school/vocational high school children. This can be seen from how to channel emotions well, have an independent attitude, and accept input and criticism well. However, there are still aspects of social maturity that are lacking, namely social skills and empathy. This research can be used as a reference by parents to apply it but still have to adjust to the child's condition. Keywords: emotional maturity; impact; tiger parenting